Analysis of the Position of Marriage Witnesses in the Opinions of the Four Madzhabs Fiqh and Regulations in Indonesia - Nasrulloh, Adang Muhamad; Nur Cholis, Mujiyo; Sucipto, Imam (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2023)
This article responds to the birth of legislation that has a correlation with marriage law as a form of uniformity and legal certainty, although there are still differences of opinion and debate among Indonesian Muslim communities regarding the position of witnesses in marriage. the discussion of witnesses to marriage is interesting to discuss, how are witnesses to marriage in the views of fiqh four madzhab and how the position of witnesses to marriage in Indonesian legislation. Using the literature review method (literature study) primary and secondary data sources from books, journals, other regulations. The results showed that first, a marriage witness according to the fiqh of four madzhab is a person who knows correctly and with certainty, his testimony can be accounted for in the future if needed by one of the spouses about the occurrence of a marriage event. The position of marriage witnesses in the legislation as a pillar of marriage, this is adopted from the opinion of the Shafi'i madzhab. Two witnesses are the minimum requirement in marriage. The purpose of requiring witnesses is to prevent negative issues from the community regarding extramarital relationships. Then the existence of marriage witnesses as a confirmation of the rights that arise after the marriage contract such as mushaharah relations, nafakah rights and inheritance rights. Keywords: Marriage Witness, Fiqh, Law.